2017
DOI: 10.1038/cti.2017.47
|View full text |Cite
|
Sign up to set email alerts
|

Immune checkpoint inhibition: prospects for prevention and therapy of hepatocellular carcinoma

Abstract: The global prevalence of liver cancer is rapidly rising, mostly as a result of the amplified incidence rates of viral hepatitis, alcohol abuse and obesity in recent decades. Treatment options for liver cancer are remarkably limited with sorafenib being the gold standard for advanced, unresectable hepatocellular carcinoma but offering extremely limited improvement of survival time. The immune system is now recognised as a key regulator of cancer development through its ability to protect against infection and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 129 publications
(273 reference statements)
0
43
0
Order By: Relevance
“…These higher rates of Grade 3‐4 adverse events likely reflect additive effects of tissue autoantigen release as a result of tumour infiltration and/or viral damage in conjunction with ICI‐induced increase of autoreactive T cell activity. There have been a growing number of published studies designed to determine the effects of ICIs for the treatment of HCC . In one clinical study, HCC patients undergoing CTLA‐4 blockade with tremelimumab who were infected with HCV demonstrated a relatively good liver adverse event profile with only transient elevations of serum aminotransferases after the first dose of therapy …”
Section: Clinical Trials Of Icis: Results Of Risk For Hepatotoxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…These higher rates of Grade 3‐4 adverse events likely reflect additive effects of tissue autoantigen release as a result of tumour infiltration and/or viral damage in conjunction with ICI‐induced increase of autoreactive T cell activity. There have been a growing number of published studies designed to determine the effects of ICIs for the treatment of HCC . In one clinical study, HCC patients undergoing CTLA‐4 blockade with tremelimumab who were infected with HCV demonstrated a relatively good liver adverse event profile with only transient elevations of serum aminotransferases after the first dose of therapy …”
Section: Clinical Trials Of Icis: Results Of Risk For Hepatotoxicitymentioning
confidence: 99%
“…There have been a growing number of published studies designed to determine the effects of ICIs for the treatment of HCC. [59][60][61][62][63][64] In one clinical study, HCC patients undergoing CTLA-4 blockade with tremelimumab who were infected with HCV demonstrated a relatively good liver adverse event profile with only transient elevations of serum aminotransferases after the first dose of therapy. 65…”
Section: Studies With Single-agent Ici Treatment Protocolsmentioning
confidence: 99%
“…have shown that human umbilical vein endothelial cells and bronchial mucosa endothelial cells can also express IL‐25 . In the liver, hepatic IL‐10/IL‐33, TNF‐β and PD‐L1 may be produced by liver sinusoidal endothelial cells . We determined the direct effect of IL‐25 on mouse liver sinusoidal endothelial cells in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…42 In the liver, hepatic IL-10/IL-33, 43 TNF-b 44 and PD-L1 45 may be produced by liver sinusoidal endothelial cells. 46 We determined the direct effect of IL-25 on mouse liver sinusoidal endothelial cells in vitro. After treatment, IL-25 induced a notable upregulation of IL-10 expression and a slight upregulation of IL-25 expression; however, IL-25 did not affect the expression of IL-33, TNF-b or PD-L1 (Supplementary figure 7f).…”
Section: Discussionmentioning
confidence: 99%
“…The multikinase inhibitors sorafenib and regorafenib are the only systemic treatments with proven survival benefits and they prolong the life expectancy of patients by 2 to 3 months (4). Immune-based approaches, including targeting of the immune checkpoint inhibitors programmed cell death (PD-1), programmed cell death ligand 1 (PD-L1) or cytotoxic T-lymphocyte-associated protein 4 (CTLA-4), represent novel, promising therapeutic strategies to prevent or treat hepatocellular carcinoma (5).…”
Section: Introductionmentioning
confidence: 99%